Seroprevalence and risk factors of equine influenza virus infection in horses of Khuzestan province - hamid Hashemi Mehrjardi; MAHDI POURMAHDI BORUJENI; alireza Ghadrdan Mashhadi; masoudreza Siefi abad shapori (Āsīb/shināsī-i Darmāngāhī-i Dāmpizishkī, 2018)
Equine influenza is an acute, infectious and highly contagious respiratory disease with worldwide distribution, high morbidity and low mortality. The disease is caused by H7N7 and H3N8 subtypes of genus A of influenza virus in the horse. The most significant clinical signs of equine influenza are fever, coughing and nasal discharge. The aim of the present study was to determine the prevalence and risk factors of Equine influenza in horses of Khuzestan province by ELISA assay. Blood samples were randomly collected from 184 horses from Ahvaz, Ramhormoz, Shush, Shushtar, Mahshahr and Abadan cities. Seroprevalence of influenza virus was 7.07% (95% CI: 3.97-10.77). Multivariate logistic regression showed that age, sex, history of respiratory disease, history of leaving the province, body condition score, type of use, herd size and geographical location justify 45 percent of fluctuations in infection. History of leaving the province was the only factor with a significant effect on infection (p